Root-to-Shoot Hormonal Communication in Contrasting Rootstocks Suggests an Important Role for the Ethylene Precursor Aminocyclopropane-1-carboxylic Acid in Mediating Plant Growth under Low-Potassium Nutrition in Tomato - Martínez-Andújar, Cristina; Albacete, Alfonso; Martínez-Pérez, Ascensión; Pérez-Pérez, José Manuel; Asins, María José; Pérez-Alfocea, Francisco (Frontiers in Plant Science, 2016)
Selection and breeding of rootstocks that can tolerate low K supply may increase crop productivity in low fertility soils and reduce fertilizer application. However, the underlying physiological traits are still largely unknown. In this study, 16 contrasting recombinant inbred lines (RILs) derived from a cross between domestic and wild tomato species (Solanum lycopersicum × Solanum pimpinellifolium) have been used to analyse traits related to the rootstock-mediated induction of low (L, low shoot fresh weight) or high (H, high shoot fresh weight) vigor to a commercial F1 hybrid grown under control (6 mM, c) and low-K (1 mM, k). Based on hormonal and ionomic composition in the root xylem sap and the leaf nutritional status after long-term (7 weeks) exposure low-K supply, a model can be proposed to explain the rootstocks effects on shoot performance with the ethylene precursor aminocyclopropane-1-carboxylic acid (ACC) playing a pivotal negative role. The concentration of this hormone was higher in the low-vigor Lc and Lk rootstocks under both conditions, increased in the sensitive HcLk plants under low-K while it was reduced in the high-vigor Hk ones. Low ACC levels would promote the transport of K vs. Na in the vigorous Hk grafted plants. Along with K, Ca, and S, micronutrient uptake and transport were also activated in the tolerant Hk combinations under low-K. Additionally, an interconversion of trans-zeatin into trans-zeatin riboside would contribute to decrease ACC in the tolerant LcHk plants. The high vigor induced by the Hk plants can also be explained by an interaction of ACC with other hormones (cytokinins and salicylic, abscisic and jasmonic acids). Therefore, Hk rootstocks convert an elite tomato F1 cultivar into a (micro) nutrient-efficient phenotype, improving growth under reduced K fertilization.